Pojavi pri varjenju z večžično elektrodo za povečanje talilnega učinka - Tušek, Janez (Materiali in tehnologije, 2002)
Arc welding with a multiple-wire electrode, particularly with a twin-wire electrode, has lately found increasing application in practice. We know submerged-arc and gas-shielded arc welding processes with a twin-wire electrode and submerged arc welding with a multiple-wire (triple wire, quadruple wire) electrode. A unit for multiple-wire welding allows welding and surfacing. A principle of multiple-wire welding is that a single welding current source, a joint wire feed mechanism, and common regulation are used while all the wires travel through the same contact tube. Weld shape can be affected by the arrangement of the wires in the contact tube with regard to the welding direction. The most important advantage of multiple-wire welding, however, is the efficiency of the electrical energy supplied. In this case, and advantage is taken of two physical phenomena, which are related but based on different principles. The first one is based on efficient utilisation of electric current when it is conducted through the wire extension, while the second one is based on a more efficient utilisation of heat energy of the arcs, i.e. more optimized energy input into a welded joint. The paper gives a description of the two physical principles accompanied by figures, theoretical calculations, and experimental results. In multiple-wire welding, welding current intensity in the wire extension varies and is practically never the same in all wires. The average value of the welding current intensity, however, is the same in each wire for the whole duration of welding. But the effective value is, due to variation of current intensity, higher than the average one, which produces a higher efficiency of the welding current. In multiple-wire welding, when the wires are arranged one after another, heat input into the workpiece has not a circular shape but an elliptical one. This increases energy efficiency and reduces heat influence on weld vicinity.
Keywords: varjenje obločno; elektrode večžične; učinki talilni; izkoristki energijski; obločno varjenje; talilno varjenje; izkoristek